Copper deficiency in dairy goats and kids - Valdir M. Almeida; Telma S. Lima; Givaldo B. Silva-Filho; Hisadora A.S.C. Bom; Silvio M.C. Fonseca; Joaquim Evêncio-Neto; Francisco A.L. Souza; Franklin Riet-Correa; Fábio S. Mendonça (Pesquisa Veterinária Brasileira, 2022)
ABSTRACT: The clinical, pathological and reproductive aspects of an outbreak of copper deficiency in dairy goats and kids from the semiarid region of Pernambuco, Brazil are described. Ten adult dairy goats with clinical signs of deficiency and four kids presenting enzootic ataxia born from copper deficient does were separated from the herd, and examined. In the dairy goats, the average serum concentration of copper was 6.1±2.8mmol/L and iron was 39.5±8.2mmol/L. In kids, the average serum concentration of copper was 3.8±0.9mmol/L and iron was 38.5±4.1mmol/L. Clinical signs in dairy goats consisted of pale mucous membranes, anemia, emaciation, diarrhea, achromotrichia, brittle hair and alopecia. The main reproductive alterations consisted of prolonged anestrus, embryonic resorption and high indices of retained placenta. The kids born from copper deficient dairy goats were weak, and presented neonatal or late ataxia until 70 days of life. Six dairy goats and four kids were necropsied. Most ovaries examined were small, firm and did not present viable follicles on their surface. Microscopically, there was reduction of viable follicles in addition to disorganization of follicular and stromal structures, with marked follicular atresia. Microscopically, changes in kids with enzootic ataxia consisted of neuronal chromatolysis and axonal degeneration, mainly in neurons of the spinal cord. In this study, the source of high iron was not identified, but it is known that outbreaks of copper deficiency can occur due to excess iron intake, mainly when adequate mineral supplementation is not provided for the goat herds.